Are human papillomavirus knowledge and vaccine uptake associated with HIV status and social determinants of health in young sexual minority men? - Trisha L. Amboree; Alan G. Nyitray; John Schneider; Nick Gargurevich; Jacky Kuo; Elizabeth Y. Chiao; Lu-Yu Hwang; Kayo Fujimoto (Preventive Medicine Reports, 2023)
This brief report examines the relationship, if any, between human immunodeficiency virus (HIV) status, and individual-level and socio-sexual partner-level factors of social determinants of health (SDOH) that are associated with human papillomavirus (HPV) knowledge and vaccine uptake in young sexual minority men (YSMM). We used data from 126 YSMM recruited by network-based sampling during 2015–2016 in Houston, Texas. Descriptive statistics and regression analyses were conducted to test the association between HIV status, SDOH, and HPV knowledge and vaccine uptake. Those living with HIV had lower odds of knowledge of HPV-associated anal cancer (OR: 0.43, 95% CI: 0.18–0.97) and knowledge of HPV spreading via sexual contact (OR: 0.11, 95% CI: 0.01–0.64), and higher odds of HPV vaccine uptake (OR: 2.90, 95% CI: 1.11–8.02). HPV knowledge and vaccine uptake in YSMM was not associated with partner’s attributes or individuals’ SDOH factors in our study yet was significantly associated with HIV status. Future interventions are needed to increase HPV knowledge among individuals living with HIV and vaccine uptake particularly among YSMM living without HIV that are not engaged in healthcare.